Comparativas de protocolos en servicios IoT - López Morales, Javier; Álvarez-Merino, Carlos Simón; Khatib, Emil Jatib; Delgado, Manuel; Barco-Moreno, Raquel (My University, 2025)
The Internet of Things (IoT) has revolutionized device interconnectivity in both industrial and home environments. How- ever, the lack of interoperability between proprietary solutions has hindered its widespread adoption. To address this, open standards such as MQTT and later Matter have emerged as leading protocols for smart home applications. This paper presents a comparative analysis of MQTT and Matter, focusing on their architectures and performance in terms of communication latency through an experimental setup designed to measure the response time of both protocols in a real-world domestic scenario.
Keywords: Internet de los objetos; Domótica; Internet of Things; Matter; MQTT; Latencia